Модель та методика моніторингу ресурсного забезпечення економічної безпеки регіону - Проскура, В. Ф. (НТУ "ХПІ", 2014)
Визначено головну мету моніторингу ресурсного забезпечення регіону, основні принципи організації його проведення а також запропоновано модель та методику моніторингу ресурсного забезпечення економічної безпеки та стійкого розвитку регіону. Запропоновані методичні підходи до основних напрямків комплексного моніторингу ресурсного забезпечення розвитку регіону, що у свою чергу визначають модель а також методику його проведення, дадуть можливість більш ефективно організувати збір інформації, об'єктивно оцінювати зміни, що відбуваються в економічній системі регіонів, прогнозувати розвиток чинників і процесів ресурсного забезпечення, своєчасно розробляти регулюючі впливи, спрямовані на підтримку позитивних і ослаблення негативних тенденцій у забезпеченні економічної безпеки та стійкого розвитку регіону.

In this article the purpose of monitoring resource support region, the basic principles of its organization and the model and method of monitoring resource providing economic security and sustainable development. The effectiveness of monitoring depends on the quality formed with the help of information, which must meet certain requirements to be transparent and useful to users in making management decisions. It is important that the quality is seen as a priority feature information, because it is a necessary condition for the stability of the market economy. The benefits to be derived from the provided monitoring information should be comparable to the cost of its preparation. The methodical approach to the main areas of complex monitoring of resource development in the region, which in turn define the model and methodology that will allow us to more effectively organize the collection of information to objectively assess changes in the economic system of the region, to predict the development of the factors and processes of resource provision, in a timely manner to develop a regulatory impact aimed at supporting positive and mitigation of negative trends in the economic security and sustainable development in the region.
Model and method of monitoring resources to ensure the economic security of the region
Keywords: регіональна економіка; регіон; економічна безпека; ресурсне забезпечення; моніторинг; region; economic security; resource provision; monitoring